QCGN Mourns Loss of James Shea, Educator and Advocate for Linguistic Duality - Quebec Community Groups Network (QCGN) (2018)

English-speaking Community Will Not Abandon School Boards, QCGN Advises Premier - Quebec Community Groups Network (QCGN) (2018)

English-speaking Blacks in Quebec : Highlights from the 2016 Census - Floch, William (2018)

Noirs d’expression anglaise au Québec : faits saillants du recensement de 2016 - Floch, William (2018)

Aesthetics : More Than What it Looks - Dawson School; Writers in the Community (2018)
Number of pages: 30

A New Path - Vanguard School; Writers in the Community (2018)
Number of pages: 36

Outlander : Stories from Inuk Boys: Surusiit Maqitiit Unikausingit - Writers in the Community (2018)
Number of pages: 47

Sippin Makes Me Cry - Writers in the Community (2018)
Number of pages: 32

Y4Y Quebec Opposes the Cancellation of the French-language University in Ontario and Expresses its Solidarity with the Young Franco-Ontarians Who Worked on the Project - Youth for Youth Québec (Y4Y Québec) (2018)

QCGN Denounces Cuts to French Language Services in Ontario - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

QFHSA Fall Conference 2018 - Quebec Federation of Home and School Associations (QFHSA) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)
Number of pages: 18

Priority Setting Steering Committee Phase II Recommendations to the Department of Canadian Heritage - Quebec Community Groups Network (QCGN) (2018)
In March 2018, the Government of Canada renewed its official languages strategy, called the Action Plan for Official Languages 2018-2023: Investing in Our Future. Amongst other investments in the Action Plan, the Department of Canadian Heritage (PCH) announced increased funding for English-language minority community organizations in Quebec. This increase is to be delivered through the Official Languages Funding Programs in two sub-components: 1) Cooperation with the Community Sector 2) a new Development Fund established specifically for English-speaking Quebec. In May 2018, the Minister of Canadian Heritage requested that representative organizations provide input on behalf of Canada’s official language minority communities, on principles and priorities for action and to guide decisions on the allocation of new financial resources for programs and projects undertaken by and for these communities through her Department. The Quebec Community Groups Network (QCGN) – English-speaking Quebec’s official interlocutor with PCH – accepted this task, and at a special meeting of its Board of Directors on June 16, tasked the Priority Setting Steering Committee (PSSC) with undertaking the work.
Keywords: Official Language Minority Community (OLMC)

Y4Y Quebec Congratulates Executive Committee Member Hayley Campbell for Winning the 2018 Young Quebecers Leading the Way Award - Youth for Youth Québec (Y4Y Québec) (2018)

La vitalité des communautés minoritaires par l'éducation, rapport sur le premier forum - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2018)
"Du 28 au 30 octobre 2018, des chercheurs, des praticiens, des intervenants communautaires et des décideurs se sont rassemblés à l’Université Concordia pour participer à un forum de trois jours axé sur la population minoritaire anglophone au Québec et intitulé La vitalité des communautés minoritaires par l’éducation. Le forum a été organisé par la Table d’éducation interordres, un comité du QUESCREN de l’Université Concordia. L’objectif du forum consistait à encourager la mobilisation en vue d’élaborer, pour les communautés d’expression anglaise au Québec, une offre éducative sensée et viable allant du niveau préscolaire aux études universitaires et favorisant la persévérance scolaire, l’accès à de bons emplois au Québec et un fort sentiment d’identité et d’appartenance."
Parallel title: Organisé par la Table d’éducation interordres (ILET), un comité du Réseau de recherche sur les communautés québécoises d’expression anglaise (QUESCREN), et tenu à l’Université Concordia du 28 au 30 octobre 2018.
Keywords: Official Language Minority Community (OLMC)

Report on the First "Minority Community Vitality Through Education" Forum - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2018)
From October 28 to 30, 2018, researchers, practitioners, community stakeholders and policymakers gathered at Concordia University for a three-day forum entitled “Minority Community Vitality Through Education,” and focused on Quebec’s English-speaking minority population. The Forum was convened by the Inter-Level Educational Table, a committee of the Quebec English-Speaking Communities Research Network (QUESCREN) at Concordia University. The objective of the Forum was to encourage mobilization around the development of a healthy and sustainable English-language educational offer in Quebec, from pre-K to university, that leads to student retention, access to good jobs in Quebec and a strong sense of identity and belonging.
Parallel title: Organized by the Inter-Level Educational Table (ILET), a committee of the Quebec English-Speaking Communities Research Network (QUESCREN), and held at Concordia University, October 28-30, 2018.
Keywords: Official Language Minority Community (OLMC)

QCGN Looks Forward to Working Together with Premier François Legault and His New Cabinet - Quebec Community Groups Network (QCGN) (2018)

Youth Internships in Community Media : A First Step Towards Capacity Building for Official Language Community Media in Minority Setting - Consortium of Official Language Minority Community Media (2018)
Keywords: Official Language Minority Community (OLMC)

An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

ELAN Quebec Thrilled with Government of Canada’s $7.5 Million Investment in Arts and Culture Micro-grants for Official Language Minority Schools - English Language Arts Network (ELAN) (2018)
Keywords: Official Language Minority Community (OLMC)

QCGN to Pay Tribute to Four Remarkable Community Leaders at 10th Anniversary Community Awards Gala - Quebec Community Groups Network (QCGN) (2018)

Partners in Health - Centre for Access to Services in English (CASE) (2018)
Number of pages: 4

Secondary School Exchanges : A Promising Way of Fostering Bilingualism in the Next Generation - Lai, Edward; Orme, Charlie; Fleming, Scott (Y4Y Québec, 2018)
In Quebec, it is a basic fact that a solid grasp of the French language is essential to finding work, participating fully in the political process, and integrating into society. While statistics show that bilingualism is very common among the Englishspeaking minority, and especially so among youth, problems nonetheless arise. Young English-speakers frequently report that they do not feel confident enough in their ability to speak French, while others remark that their written French is not strong enough to land a job. Inadequate knowledge of French is a contributing factor to the higher unemployment rates experienced by young English- speakers. A lack of work, and a hampered ability to take part in public life in general, lead to the disenfranchisement of members of this community. Given the high demand among young English- speakers for more French-language training, policy makers must come up with new and creative ways of meeting the demand.

Network News - Quebec Community Groups Network (QCGN) (2018)
Number of pages: 17

Report of the Priority Setting Steering Committee Related to the 2018 Community Consultation - Quebec Community Groups Network (QCGN) (2018)
In March 2018, the Government of Canada renewed its official languages strategy, called the Action Plan for Official Languages 2018-2023: Investing in Our Future. Amongst other investments contained in the Action Plan, the Department of Canadian Heritage (PCH), was provided resources to increase the amount of funds available to the community sector through the Cooperation with the Community Sector – Development of Official Language Communities program, and, a development fund was established specifically for English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2018)
Number of pages: 5

ELAN's 14th Annual General Meeting - English Language Arts Network (ELAN) (2018)
Keywords: Official Language Minority Community (OLMC)

Community-based Process Results in Strong Watchdog Committee for English Health and Social Services - Quebec Community Groups Network (QCGN) (2018)

QCGN Advocates a More Community-driven Process for Provincial Funding - Quebec Community Groups Network (QCGN) (2018)

Resources for Families with Special Needs - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Cabinet Shuffle Blurs Roles and Could Delay Implementation of Action Plan for Official Languages - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

Quebecers Attachment to Canada: One year after the 150th - Jedwab, Jack; Warren, Jean-Philippe (2018)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2018)
Number of pages: 4

Multiculturalism versus Interculturalism : Myth and Reality - Jedwab, Jack; Warren, Jean-Philippe (2018)

Attachment to Quebec and Recent Historic Markers - Jedwab, Jack; Warren, Jean-Philippe (2018)

QCGN Set To Champion English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

Action Plan for Official Languages 2018-2023 Highlights (2018)

English-speaking Quebec and the Provincial 2018 Election - Quebec Community Groups Network (QCGN) (2018)

Plus ça change, plus c'est pareil : Retour sur le rapport du Groupe de travail sur le réseau scolaire anglophone de 1992 - Advisory Board on English Education (2018)

Plus ça change, plus c'est pareil : Revisiting the 1992 Task Force Report on English Education in Québec - Advisory Board on English Education (2018)

Bonjour Hi : What French and English Quebecers Think About Each Other and About Key Issues - Jedwab, Jack; Warren, Jean-Philippe (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)
Number of pages: 14

The Poetic Motherhood - Writers in the Community (2018)
Number of pages: 28

Inuit Boy Stories : Carving Our Words Into Stone - Writers in the Community Program (2018)
Number of pages: 50

Annual Activity Report : June 1, 2017 - May 31, 2018 - Literacy Quebec (LQ) (2018)
Literacy Quebec provided ongoing support to its members by offering training and assistance via web, email and telephone. The LQ staff fielded and responded to 950+ enquiries and concerns from its membership. They also sent out 30 email updates throughout the year. Members were brought together once in person and once via web-conference for professional developments and networking opportunities.
Keywords: Official Language Minority Community (OLMC)

Future of English-speaking Quebecers is Core Element for Modernization of Official Languages Act - Quebec Community Groups Network (QCGN) (2018)

English-speaking Quebec and the Modernization of the Official Languages Act : Brief Submitted to the Standing Senate Committee on Official Languages Study on Canadians' Views about Modernizing the Official Language Act - Sandilands, Marion (Quebec Community Groups Network (QCGN), 2018)
The Quebec Community Groups Network (“QCGN”) welcomes this opportunity to contribute to this Committee’s study on modernizing the Official Languages Act (“the Act”). In the spirit of modernization, the QCGN takes this opportunity to present a picture of the contemporary English-speaking community of Quebec. As this Committee noted in 2011, there are certain widely-held myths regarding this community. The QCGN hopes to contribute to a modernized understanding of this community and its role as a unique and important official language minority community in Canada.
Keywords: Official Language Minority Community (OLMC)

Don't Judge a Cover - Dawson Alternative (2018)
Number of pages: 38

Understand - Dawson Alternative School (2018)
Number of pages: 28

ELAN presents Arts Alive! Québec : Successful Multi-region Arts Festival Returns for 4th Exciting Year - English Language Arts Network (ELAN) (2018)

This Small Town - Harrington School; Writers in the Community (2018)
Number of pages: 26

One Land Divided By Lines Not Seen : Poems by Netagamiou School Secondary IV and V - Netagamiou School (2018)
Number of pages: 44

Growing Between the Cracks - Writers in the Community (2018)
Number of pages: 34

74th Annual General Meeting & Awards Banquet - Quebec Federation of Home and School Associations (QFHSA) (2018)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2018)
Parallel title: Education in the 21st Century

Quebec Federation of Home and School Associations By-Laws - Quebec Federation of Home and School Associations (QFHSA) (2018)

Guide to the Development of Access Programs for Health and Social Services in the English Language - Kosseim, Mylène; Prata, Ghislaine (Community Health and Social Services Network (CHSSN), 2018)
This Guide provides institutions with a common provincial framework It describes the steps institutions must follow to develop their access program for health and social services in the English language (hereafter “access program”). It takes three key principles into consideration: the relationship between effective communication and successful clinical interventions; the needs expressed by the English-speaking community with respect to access to health and social services in their language; the assessment of results in a context of continuous improvement.

QCGN/Community Pleased with Funding from Secretariat - Quebec Community Groups Network (QCGN) (2018)

Long Awaited Regulation Creating Provincial Access to Committee a First Step in the Right Direction - Quebec Community Groups Network (QCGN) (2018)

An Adapted Approach to Supporting English-Speaking Children (0-5) and Families in the Province of Quebec - Community Health and Social Services Network (CHSSN) (2018)
The primary objective of this document is to further encourage and inspire English-speaking communities to collaborate with stakeholders in their regions offering programs and services to children and families. The document may also serve as a useful tool for stakeholders to become more aware of specific needs often faced by Englishspeaking children and their families and learn about some of the adapted approaches and initiatives underway.

Visions of Hope - Dawson Alternative School (2018)
Number of pages: 10

Décrochage scolaire au Québec : Dix ans de surplace, malgré les efforts de financement - Institut du Québec; Le Conference Board du Canada; HEC Montréal (2018)
La plupart des tests internationaux indiquent que le système éducatif québécois se compare favorablement aux provinces canadiennes et aux pays de l’OCDE. Compte tenu du retard de scolarisation du Québec dans les années 1960, il faut saluer ces succès indéniables. Toutefois, malgré les progrès importants réalisés depuis les réformes découlant du Rapport Parent, un problème majeur persiste : le taux de diplomation dans les écoles publiques québécoises est encore très faible, et surtout il stagne depuis plusieurs années.

Network News - Quebec Community Groups Network (QCGN) (2018)
Number of pages: 11

Recommendations from the Youth Unemployment Forum Held on December 5, 2017 - Youth Employment Services (YES) (2018)
In Quebec and indeed across Canada we are confronting the many and varied challenges of a rapidly evolving labour market. New technologies are developing at a rate that is challenging our institutions; globalization is bringing increasing unpredictability to economic systems; traditional management models are being disrupted by the growing sharing and gig economies. Youth may have adapted quickly to high-tech society, however it would be disastrous to assume they will adjust as easily to the trials of the Fourth Industrial Revolution. Today’s youth need innovative supports to help them to survive in and capitalize on the complexities of the future economy. While Québec youth have never been more highly educated or bilingual, young job seekers andemployers alike are frustrated. Not enough has been done to curb the outmigration of educated youth nor to create an equitable environment for underrepresented populations. It hardly matters that jobs may be available, if youth are not here or not able to connect with them. This is why, with support from Canadian Heritage, on December 5th, 2017 YES convened a daylong forum bringing together multiple sectors from throughout the province of Quebec, to develop a deeper understanding of the unique employment barriers faced by Quebec’s Official Language Minority Community (OLMC) youth.
Keywords: Official Language Minority Community (OLMC)

Application for Public Reading(s) by English-language Writers Published by AELAQ Members : Funded by the Canada Council for the Arts - Association of English-language Publishers of Quebec (AELAQ) (2018)

QCGN Welcomes New Federal Investments in English-speaking Quebec - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes New Budget Measures for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2018)

Demographic Profile of the English-speaking Communities : Administrative Region of Montréal & the Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laval & the Rest of Quebec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Network News - Quebec Community Groups Network (QCGN) (2018)
Number of pages: 11 issued: February, 2018/March, 2018

QCGN Welcomes Promises of New Investments in Official Languages - Quebec Community Groups Network (QCGN) (2018)

Impact of the 2011-2014 Community Leadership Bursary Program : Adjustments for the future? - Gagnon, Marie-Pierre; Lampron, Amélie (2018)

Re: Broadcasting Notice of Consultation CRTC 2017-183, Renewal of Société de télédiffusion du Québec licence, 2017-0830-7 - English Language Arts Network (ELAN); Rodgers, Guy (2018)
Keywords: Official Language Minority Community (OLMC)

CAQ Misses the Mark with Scheme to Abolish School Boards - Quebec Community Groups Network (QCGN) (2018)

Request for Proposals: Communications Specialist to Develop Outreach Plans & Tools to Promote Micro Grants Program for Arts & Culture in English Schools in Quebec - English Language Arts Network (ELAN) (2018)

QCGN Social Media Guidelines - Quebec Community Groups Network (QCGN) (2018)
Social media has changed the way we communicate. Increasingly, our community learns about the Quebec Community Groups Network on Facebook and Twitter. It’s where our community and our critics leave their comments, applaud, and sometimes condemn our work. It’s an important, interactive communications tool that we must learn to harness and use strategically. Over the past five years, the QCGN and many of its members have established a solid and growing digital presence that has connected us with more and more members of our community. Social media provides an interactive space where we can proactively spread relevant news and views, share happenings from across our Network with members and partners, ask and answer questions, and connect with important community and political stakeholders. It is also a place where we can garner support and gather feedback.

Eyelash : A Literary Zine - Writers in the Community (2018)
Number of pages: 38

Reader's Report and Invoice - Association of English-language Publishers of Quebec (AELAQ) (2018)
issued: 2018/2019

Annual Report 2017-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Building Confidence : Conversing with the English Community : A How-to Toolkit - Community Health and Social Services Network (CHSSN) (2018)

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2018)
Number of pages: 6

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2018)
Number of pages: 9

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2018)
Number of pages: 8

Community NetLink - Community Health and Social Services Network (CHSSN) (2018)
Number of pages: 6

Investment Priorities 2013-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Key Demographic and Socio-economic Characteristics of Quebec's English-speaking Youth (15-29) - Community Health and Social Services Network (CHSSN) (2018)
This CHSSN report profiles the situation of English-speaking citizens of Quebec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for the vast majority of Quebecers aged 15-29, these milestones are completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policy-makers and program managers through to public institutions and community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Quebec’s citizens.
Keywords: Official Language Minority Community (OLMC)

Pour gagner en assurance : Conversation avec la communauté d’expression anglaise - Community Health and Social Services Network (CHSSN) (2018)

Année scolaire 2017-2018 : Programme de bourses de leadership communautaire en santé et services sociaux - Dialogue McGill (2018)

Main Achievements 2014-2018 - Dialogue McGill (2018)

Profil des rélisations 2014-2018 - Dialogue McGill (2018)

In Quebec & Tour Ready : A Booklet of 41 Quebecois Performing Artists and Their Tour Ready Work - English Language Arts Network (ELAN) (2018)

CLC Extended Model : Learnings & Next Steps from the First 4 Years - Estuaries Learning Consulting Group (Leading English Education and Resource Network (LEARN), 2018)

CLC Extended Model : Learnings & Next Steps from the First 4 Years - Estuaries Learning Consulting Group (Leading English Education and Resource Network (LEARN), 2018)
From January to March of 2018, LEARN undertook an evaluation of the CLC extended model that looked to answer two key questions: 1) Has the CLC extended model been a success, and; 2) What best practices can schools and school boards adopt to effectively introduce the CLC extended model? In asking these questions, LEARN was looking to support two specific types of stakeholders: 1) Schools and school boards wanting to understand the benefits and outcomes of the extended model; and, 2) Schools and school boards wanting a deeper understanding of how to extend effectively. The majority of school boards currently have CLCs that have been extended models for a short duration. The data presented here reflects this, as it responds to question two more fully. It will be useful to do a further evaluation in a few years’ time to gather more precise data on the success of the model, once schools have engaged with it for a longer period.

Key Demographic and Socio-Economic Characteristics of Quebec's English-speaking Youth (25-29) - JPocock Research Consulting (Community Health and Social Services Network (CHSSN), 2018)
This CHSSN report profiles the situation of English-speaking citizens of Quebec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood.

[CLC Health & Wellbeing Pathway Template] - Leading English Education and Resource Network (LEARN) (2018)

Teaching and Learning with Stories - Leading English Education and Resource Network (LEARN) (2018)
Number of pages: 381

Message For Our Veterans - Maurice, Cornella (2018)

Grant Writing Principles - Park, June (2018)

Participation of English-speaking Canadians in the Federal Civil Service in Quebec (outside of the National Capital Region) - Quebec Community Groups Network (QCGN) (2018)

Regional Priorities : QCGN Members 2018 - Quebec Community Groups Network (QCGN) (2018)
This document is a collaborative effort on the part of the regional member organization's of Quebec Community Groups Network to ensure regional priorities are at the fore of the Priority Setting Steering Committee discussions and to establish preferred and inclusive methods of consultation among regional member groups.

Changes to Article II Constitution : Resolution 2018-03 - Quebec Federation of Home and School Associations (QFHSA) (2018)

Changes to QFHSA By-Laws-Addition of Article XIII Dissolution : Resolution 2018-04 - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)
Number of pages: 24

Resolution 2018-01 : Healthy Sleep and Late School Start Time - Quebec Federation of Home and School Associations (QFHSA) (2018)

Resolution 2018-02 : Wider Access to English Education - Quebec Federation of Home and School Associations (QFHSA) (2018)
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2017-2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Programme de maintien en poste : Monitoring des stagiaires - Storr, Caroline; Hendrickson, Mary (2018)

Retention Program : Monitoring of Internship Students - Storr, Caroline; Hendrickson, Mary (2018)

9 Quick Safety Tips to Manage Your Medications - Trimble, Johanna; Currie, Janet (2018)

Mieux gérer vos médicaments : 9 conseils utiles - Trimble, Johanna; Currie, Janet (2018)